2021
DOI: 10.1039/d1em00102g
|View full text |Cite
|
Sign up to set email alerts
|

Exploring variations of hexabromocyclododecane concentrations in riverine sediments along the River Medway, UK

Abstract: Surface riverine sediment samples were collected along the course of the River Medway, UK between Yalding and the mouth of the estuary at 40 different sites. The samples were then...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…1,15 It has been reported that HBCDDs can leach from textiles even at room temperature. 16 As a result, they are globally distributed in various environmental samples such as indoor and outdoor air, [17][18][19] surface water, 5,20,21 wastewater and sewage sludge, 22,23 sediments, 24,26 soil and road dust, 6,27,28 indoor dust, 19,29,30 food, [31][32][33] and biota. 34,35 In addition, several biomonitoring studies have detected HBCDDs in human tissues such as human milk, [36][37][38] serum, 39,40 and hair, 41,42 indicating human exposure to HBCDDs.…”
Section: Introductionmentioning
confidence: 99%
“…1,15 It has been reported that HBCDDs can leach from textiles even at room temperature. 16 As a result, they are globally distributed in various environmental samples such as indoor and outdoor air, [17][18][19] surface water, 5,20,21 wastewater and sewage sludge, 22,23 sediments, 24,26 soil and road dust, 6,27,28 indoor dust, 19,29,30 food, [31][32][33] and biota. 34,35 In addition, several biomonitoring studies have detected HBCDDs in human tissues such as human milk, [36][37][38] serum, 39,40 and hair, 41,42 indicating human exposure to HBCDDs.…”
Section: Introductionmentioning
confidence: 99%